Nurses' and Managers' Perceptions of the Transition of Older Adults From Long-Term Care Facilities to the Emergency Department: A Mixed-Methods Study / Perceptions du personnel infirmier et du personnel cadre sur la transition des aînés des établissements de soins de longue durée vers l’urgence : une étude à méthodes mixtes - Peguero-Rodriguez, Gabriela; Polomeno, Viola; Backman, Chantal; Chartrand, Julie; Lalonde, Michelle (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence, 2025)
Problem: Several challenges are present with the transition of older adults from a long-term care facility (LTCF) to the emergency department (ED). Nurses play an important role in the LTCFs and the EDs during this transition.Objective: To describe the perceptions of nurses and managers in relation to this transition.Methods: This study used a sequential mixed methods design. An online questionnaire was distributed to LTCF and ED nurses during Phase 1 (quantitative). During Phase 2 (qualitative), semi-structured interviews were conducted with nursing management in these two settings. Descriptive statistics were used as well as t-tests, to compare the perceptions between the LTCF and the ED nurses. Thematic analysis was used for the qualitative data.Results: After the analysis of the questionnaire’s responses (n=38), the nurses from the LTCFs and the EDs had similar perceptions and considered the transition of older adults from the LTCF to the ED as not occurring effectively, and the inter-institutional communication was not efficient. Following the interviews conducted with nursing management (n=7), four themes were identified, reflecting the limitations of LTCFs in caring for the older adults, the obstacles associated with the transfer of information, the consequences of an ED stay for older adults, and the contribution of caregivers.Conclusion: Four key conclusions can be drawn: 1. transitions are influenced by the LTCF material and human resources; 2. the transfer of information is inefficient; 3. the ED environment is not adapted for the needs of older adults; and 4. the integration of caregivers is important but does present with challenges.